1973
DOI: 10.1002/jlac.19727650113
|View full text |Cite
|
Sign up to set email alerts
|

Über zweistufige Redoxsysteme, IX1) Polarographie2) und Spektroskopie heterocyclisch substituierter Äthylene und ihrer höheren Oxidationsstufen

Abstract: Die Systeme 1 und 2 sowie 2B bis 4B zeigen zweistufige Polarogramme, aus denen sich Semichinonbildungskonstanten K = 102-1014 ableiten lassen. Der Einflul3 der Struktur auf K sowie die Lage von El und E2 werden diskutiert. Nur fur 2 und 2B sind Elektronenspektren der Stufen Red, Sem und Ox zu erhalten. Two-step Redox Systems, IX1). -Polarography and Spectroscopy of Heterocyclic Substituted Ethylenes and Their Higher Oxidation LevelsThe systems 1, 2, 2B to 4B display two-step polarograms from which semiquinone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Our recent research has probed the ground‐state donor properties of highly reactive neutral organic reducing agents. Thus, we have shown that the neutral ground‐state organic electron donor 1 7, 8 (Scheme ) reduces iodoarenes9, 10 to aryl radicals11 while the stronger donors 2 12 and 3 13 under milder conditions, afford aryl anions from the same substrates through transfer of two electrons. These donors also reduce sulfonamides, acyloin derivatives, and Weinreb amides 13…”
Section: Methodsmentioning
confidence: 96%
“…Our recent research has probed the ground‐state donor properties of highly reactive neutral organic reducing agents. Thus, we have shown that the neutral ground‐state organic electron donor 1 7, 8 (Scheme ) reduces iodoarenes9, 10 to aryl radicals11 while the stronger donors 2 12 and 3 13 under milder conditions, afford aryl anions from the same substrates through transfer of two electrons. These donors also reduce sulfonamides, acyloin derivatives, and Weinreb amides 13…”
Section: Methodsmentioning
confidence: 96%
“…Whereas tetrathiafulvalenes and analogues [ 1 5 ] have principally found widespread applications in materials science, tetraazaalkenes and related compounds are much more reactive and are of potential or actual interest as reagents in synthesis [ 6 33 ]. Among the tetraazaalkenes, those that are converted to aromatic molecules upon oxidation, e.g., tetraazafulvalenes 1 and 2 , are extremely reactive, and their electrochemical properties have been studied in some depth [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we have shown that the neutral ground-state organic electron donor 1 [7,8] (Scheme 1) reduces iodoarenes [9,10] to aryl radicals [11] while the stronger donors 2 [12] and 3 [13] under milder conditions, afford aryl anions from the same substrates through transfer of two electrons. These donors also reduce sulfonamides, acyloin derivatives, and Weinreb amides.…”
mentioning
confidence: 98%
“…Thus, we have shown that the neutral ground-state organic electron donor 1 [7,8] (Scheme 1) reduces iodoarenes [9,10] to aryl radicals [11] while the stronger donors 2…”
mentioning
confidence: 99%